Deskripsi Kemampuan Koneksi Matematis pada Materi Sistem Persamaan Linear Dua Variabel Ditinjau dari Gaya Kognitif Siswa SMP Kelas IX - Nurdin Arsyad; Rahmat Syam; Asep Ardat (Issues in Mathematics Education (IMED), 2017)
This research was qualitative descriptive research that aims to describe the ability of students’ mathematical connection toward cognitive style. Subject as much 2 students SMP of grade IX. Instruments of this research were GEFT (Group Embedded Figure Test) test and mathematical connection ability test. The results of this study indicate ISWA’s ability to solve problems by two capability indicators connection mathematically studied. (1) Linkages between concept mathematics. (2) Linkages mathematics with daily life situation. The results of data analysis show that ability connection mathematical students corresponding with style the cognitive they possess on the material system two linear equations variable namely on the indicator first , the subject with style cognitive field independent have high level of mathematical connection ability while subject with style cognitive field dependent have medium level of mathematical connection ability. On the second indicator of mathematical connection ability, the subject with style cognitive field independent and subject with style cognitive field dependent have high level of mathematical connection ability.